Enhancing Young Learners' Vocabulary Acquisition and Engagement Through Nursery Rhymes in Early Childhood Education - Rina Eliyanti; Apolonius Anas; Ouda Teda Ena; Barli Bram (Murhum : Jurnal Pendidikan Anak Usia Dini, 2026)
This Classroom Action Research (CAR) was motivated by the low English vocabulary mastery among 38 students at Santo Agustinus B Kindergarten. The purpose of this study was to investigate the extent to which the use of children's songs improves students' receptive and expressive vocabulary mastery, and its impact on active participation. The researchers conducted a classroom action research involving 38 students. Qualitative and quantitative methods, including tests and observation checklists, were used in three cycles. The results showed a significant increase in vocabulary mastery; the average score of receptive ability increased from 32.8 in the pre-test to 94.2 in the third cycle, while expressive ability increased from 32.5 to 93.2. Although the use of songs initially caused distraction due to overexcitement, the integration of visual cues and Total Physical Response (TPR) in subsequent cycles successfully stabilized students' concentration. The study concluded that the use of children's songs effectively increased students' active engagement and vocabulary mastery, while creating a more enjoyable and less challenging English learning process for early childhood.